Exploring The Factors Influencing the Adoption of ChatGPT in Educational Institutions: Insights from Innovation Resistance Theory - Alghamdi, Salem; Alhasawi, Yaser (Journal of Applied Data Sciences, 2024)
The ability of ChatGPT to increase student interaction and personalize learning has the capacity to dramatically change educational institutions. It can help students to ask questions and receive immediate answers from their teachers, provide personalized feedback, as well as provide dynamic experiential learning. This research explores the factors affecting the intention to use ChatGPT for educational purposes, based on Innovation Resistance Theory (IRT). A structural equation modeling was used to analyze data that was gathered from 340 American learners. The results show that usage barrier construct, value barrier, risk barrier, image barrier, traditional barrier, and perceived cost barriers are negatively associated with the intention to use ChatGPT. These findings have important ramifications for ChatGPT developers, educators, and academic institutions. Educators can leverage ChatGPT's capabilities to enhance student learning experiences, facilitate personalized learning paths, and foster collaborative learning environments.